2003
DOI: 10.1002/jpln.200390032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of load on shrinkage behavior of peat soils

Abstract: The shrinkage of the peat soils that accompanies the soil moisture changes is an important feature of such soils and has strong influence on their physical attributes and soil water management. The relationships between soil moisture and volume are often described using shrinkage characteristic curves by relating void ratio (volume of voids per unit volume of solids) to moisture ratio (volume of water per volume of solids). For conversion of soil volume changes into cracks volume and subsidence, a dimensionles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 0 publications
4
39
0
Order By: Relevance
“…Therefore, the peat layers below the phreatic zone have to bear an increased weight, as the weight of the overlying material is transferred from the liquid to the peat fibres, causing compression (Sauerbrey and Zeitz 1999). Additionally, higher desiccation intensities due to the lowering of the groundwater table and less capillary rise occur, leading to shrinkage processes (Brandyk et al 2002;McLay et al 1992;Oleszczuk et al 2003;Schwärzel et al 2002). (2) Typical mineralisation rates of drained fen peats in Northern Germany reach up to 1 cm year −1 (Göttlich 1990).…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, the peat layers below the phreatic zone have to bear an increased weight, as the weight of the overlying material is transferred from the liquid to the peat fibres, causing compression (Sauerbrey and Zeitz 1999). Additionally, higher desiccation intensities due to the lowering of the groundwater table and less capillary rise occur, leading to shrinkage processes (Brandyk et al 2002;McLay et al 1992;Oleszczuk et al 2003;Schwärzel et al 2002). (2) Typical mineralisation rates of drained fen peats in Northern Germany reach up to 1 cm year −1 (Göttlich 1990).…”
Section: Introductionmentioning
confidence: 96%
“…Land subsidence in peatlands is a consequence of drainage that results in shrinkage due to the loss of volume occupied by the water and rearrangement of the particles when the water is removed (Oleszczuk et al 2003), and organic matter oxidation (Sanei et al 2005). The oxidation of the organic matter can result in humification or mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…Shrinkage refers to the loss of volume occupied by the water (through vertical and horizontal drainage and evapotranspiration) and rearrangement of the particles (including compaction) when the water is removed (Arnold & Ghezzehei 2015, Ilnicki 2002, Oleszczuk et al 2003). …”
Section: Role Of Water Loss In Subsidence Of Dredged Sediment Drainagmentioning
confidence: 99%
“…Land subsidence in these areas is, in addition to long term geological effects, mostly a consequence of anthropogenic interference such as drainage which results in shrinkage due to the loss of volume occupied by the water and rearrangement of the particles (Oleszczuk et al 2003), and in organic matter oxidation (Sanei et al 2005). There are studies with contrasting results regarding the individual contribution of shrinkage and organic matter oxidation to the total land subsidence: some report that the high subsidence rates observed in the layer above the groundwater level is mostly oxidation of organic matter (Dawson et al 2010, Hoogland et al 2012, Schothorst 1977; others relate land subsidence mainly with shrinkage (Teatini et al 2011); and other studies concluded that the contribution of oxidation of organic matter and shrinkage is variable in time (Hooijer et al 2012, Pronger et al 2014, van Asselen 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation